(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Infertility is generally regarded as a major clinical problem, and it adversely affects people both psychologically and medically. In this study, the changes in gonadal oxidative stress markers and reproductive function of BALB/c mice were investigated. Forty-eight (48) BALB/c mice acquired for this study were randomly divided into four (4) groups of eight (8) mice each. Each group was further sub-divided into male and female groups with equal number of mice. The groups were represented as thus: Group A: normal mice; Group B: mice infected with Plasmodium berghei; Group C: Plasmodium berghei infected mice treated with Artemether/Lumefantrine; Group D: Plasmodium berghei infected mice treated with Vitamin E. The experimental mice were inoculated with the Plasmodium berghei, and the parasites were confirmed in the mice four days later before the commencement of the experiments. After the experimental procedures which lasted for fourteen (14) days, the mice were sacrificed, blood samples collected for serum testosterone, estrogen and progesterone assay; semen were collected for semen analysis; and testes and ovaries were harvested for histological analyses and oxidative stress marker determination. Result show that Plasmodium berghei significantly (p<0.05) decreased the sperm count, percentage of sperm with progressive motility and percentage of sperm with normal morphology. The parasites also decreased the serum concentrations of testosterone and progesterone. Plasmodium berghei, also caused significant (p<0.05) reductions in testicular and ovarian activities of superoxide dismutase, glutathione and peroxidase catalase while significantly (p<0.05) increasing the malonaldehyde level. The parasites also caused marked histological distortions in the testes and ovaries of the mice. Treatment with Artemether/Lumefantrine and Vitamin E separately reversed the detrimental changes induced by the parasites by increasing the semen quality and hormonal concentrations. Treatment with Artemether/Lumefantrine and Vitamin E also decreased the oxidative stress level of the gonads and improved the histological features of the testes and ovaries of the infected mice. This study therefore showed Plasmodium berghei infection posed anti-fertility threat while treatment with Artemether/Lumefantrine and Vitamin E ameliorates the effect of the parasites.